Prophet Muhammad: the CIO of the Ummah - Zulhuda, Sonny (Republika, 2024)
'Informatics' is a known computing term relating to the science of processing data for storage and retrieval. The term is also defined as things related to information: it is the science of collecting, classifying, storing, issuing, and disseminating knowledge. Prophetic informatics in this article is meant as the Prophet Muhammad's efforts in managing data and information both internally and externally in the context of his prophetic mission. There are many lessons we can learn from the teachings of the Prophet Muhammad in managing information assets so that he successfully carried out his nobel mission both in the Mecca and Medina phases. This prophetic informatics legacy needs to be continuously studied, analyzed and then formulated and emulated. It is no exaggeration that the success of Muhammad's propagation was supported by excellent information management by him with the support of his companions. Data, information and knowledge were managed in all aspects, namely the acquisition, retention/storage and use of information.